Overview of Work Engagement with Remote Worker - Muhammad Ali Adriansyah; Firda Apriliana; Elling Rikza Nadzifah; Annisa Afifah Febrianti; Shinta Aprillia Pramesti (International Journal of Social Science and Business, 2023)
Work from home, or WFH, has been implemented since the COVID-19 pandemic. WFH, or work from home, has existed since the past, but it is not used in COVID-19 and is used in normal situations. With the work-from-home, the system also changed. This system was called a Remote worker. This study aims to analyze the description of remote workers experienced by workers. This type of research was qualitative research with phenomenological methods. Data collection methods used interviews and observation. The data collection technique used was the purposive sampling technique. While the data analysis techniques used consisted of preparing the data, reading the entire data, coding the data, applying the results of data coding into themes to be analyzed, presenting the themes in narrative form, and interpreting the data. The results showed that the four subjects, NH, MR, ISF, and LA, experienced increased motivation in remote workers. Other findings show that while working from home, the subject had good productivity and work resilience. It was influenced by factors within each of them when they decided to work remotely. Based on the results of the study, it can be concluded that remote workers have an increase in motivation through work from home (WFH). In addition, it was found that remote workers are more productive and have good fighting power. These findings reinforce that remote work also makes workers engaged in work even more engaged.